Molecular Characterization of an Endozoicomonas-Like Organism Causing Infection in the King Scallop (Pecten maximus L.) - Cano, Irene (Appl Environ Microbiol, 2018)
One of the fastest growing fisheries in the UK is the king scallop (Pecten maximus L.), also currently rated as the second most valuable fishery. Mass mortality events in scallops have been reported worldwide, often with the causative agent(s) remaining uncharacterized. In May 2013 and 2014, two mass mortality events affecting king scallops were recorded in the Lyme Bay marine protected area (MPA) in Southwest England. Histopathological examination showed gill epithelial tissues infected with intracellular microcolonies (IMCs) of bacteria resembling Rickettsia-like organisms (RLOs), often with bacteria released in vascular spaces. Large colonies were associated with cellular and tissue disruption of the gills. Ultrastructural examination confirmed the intracellular location of these organisms in affected epithelial cells. The 16S rRNA gene sequences of the putative IMCs obtained from infected king scallop gill samples, collected from both mortality events, were identical and had a 99.4% identity to 16S rRNA gene sequences obtained from “Candidatus Endonucleobacter bathymodioli” and 95% with Endozoicomonas species. In situ hybridization assays using 16S rRNA gene probes confirmed the presence of the sequenced IMC gene in the gill tissues. Additional DNA sequences of the bacterium were obtained using high-throughput (Illumina) sequencing, and bioinformatic analysis identified over 1,000 genes with high similarity to protein sequences from Endozoicomonas spp. (ranging from 77 to 87% identity). Specific PCR assays were developed and applied to screen for the presence of IMC 16S rRNA gene sequences in king scallop gill tissues collected at the Lyme Bay MPA during 2015 and 2016. There was 100% prevalence of the IMCs in these gill tissues, and the 16S rRNA gene sequences identified were identical to the sequence found during the previous mortality event. IMPORTANCE Molluscan mass mortalities associated with IMCs have been reported worldwide for many years; however, apart from histological and ultrastructural characterization, characterization of the etiological agents is limited. In the present work, we provide detailed molecular characterization of an Endozoicomonas-like organism (ELO) associated with an important commercial scallop species.